Grain Sorghum Cost-Return Budget in Southeast Kansas - Dumler, Troy J.; Shoup, Douglas (My University, 2011)
This publication outlines the expected costs and returns for grain sorghum production in southeast Kansas.
MF995_2011_12
Keywords: MF995; Economics; Crops; MF